Development Strategy for the Core Software and Hardware of Artificial Intelligence in China - Gao Lei, Fu Yongquan, Li Dongsheng, Liao Xiangke (《中国工程科学》杂志社, 2021)
Artificial intelligence (AI) is an important enabling technology for promoting global digital development, and it is leading a new round of technological revolution and industrial transformation. Promoting AI core software and hardware technologies and industry is strategically significant for the national development, industrial upgrading, and productivity improvement in China. In this study, we summarize the development status of AI core hardware and software in China and abroad from the aspects of technology, industry, and policy, and analyze the problems faced by China’s development. Subsequently, we present the development ideas of China’s AI hardware and software technology and industry, propose the strategic objectives for 2025 and 2035, and summarize the key tasks for future development from the aspects of AI core hardware, AI core software, and AI-related basic technology. To provide references for the sustainable development of AI core hardware and software in China, we suggest that AI core software and hardware technologies should be included in the national top-level planning for science and technology innovation to acquire increased scientific research investment; AI open source platforms should be constructed and demonstrated; the research and development of AI key generic technologies should be promoted to achieve collaborative innovation; the AI industrial base should be reengineered to upgrade the industrial chain; and the AI innovative talent training system should be improved.